LIBRARY AND INFORMATION SCIENCE: A STUDY ON OPEN ACCESS JOURNALS IN LIBRARIES - Shantaram, Pranesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present paper tries throwing light online resource in library. Due to open access Journals brought revolutionary changes in library services. This paper was study the impact of ICT in library services. The paper explains some gateways of open access journals movement and special reference to DOAJ. Open access spurred by the Internet has brought in new vistas for dissemination of scholarly content in almost all the disciplines. It has enabled agencies, publishers and individuals to distribute scholarly content online, free from licensing restrictions and cost. Like other fields, the growth of open access has also benefited the field of library and information science (LIS). In this paper an attempt has been made to assess the current status of open access journals in LIS covered in Directory of Open Access Journals (DOAJ) based on various parameters.